British society of gastroenterology Endoscopy Quality Improvement Programme (EQIP): overview and progress. Issue 2 (18th January 2019) - Rees, Colin J; Koo, Sara; Anderson, John; McAlindon, Mark; Veitch, Andrew M; Morris, Allan John; Bhandari, Pradeep; East, James E; Webster, George; Oppong, Kofi W; Penman, Ian D
Abstract : High quality gastrointestinal (GI) endoscopy improves patient care. Raising standards in endoscopy improves diagnostic accuracy, management of pathology and ultimately improves outcomes. Historical identification of significant variation in colonoscopy quality led to the development of the Joint Advisory Group (JAG) on GI Endoscopy, the Global Rating Scale (GRS), JAG Endoscopy Training System (JETS) training and certification. These measures led to major improvements in UK endoscopy but significant variation in practice still exists. To improve quality further the British Society of Gastroenterology Endoscopy Quality Improvement (EQIP) has been established with the aim of raising quality and reducing variation in the quality of UK endoscopy. A multifaceted approach to quality improvement (QI) will be undertaken and is described in this manuscript. Upper GI EQIP will support adoption of standards alongside regional upskilling courses. Lower GI EQIP will focus on supporting endoscopists to achieve current standards alongside approaches to reducing postcolonoscopy colorectal cancer rates. Endoscopic retrograde cholangiopancreatography EQIP will adopt a regional approach of using local data to support network-based QI. Newer areas of endoscopy practice such as small bowel endoscopy and endoscopic ultrasound will focus on identifying key performance indicators as well as standardising training and accreditation pathways. EQIP will also support QI in management of GI bleeding as well as standardising the approach to new techniques and technologies. Where evidence is lacking, approaches to gather new evidence and support the translation into clinical practice will be supported.